2007
DOI: 10.1073/pnas.0610590104
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Metabolic regulation of SIRT1 transcription via a HIC1:CtBP corepressor complex

Abstract: The Sir2 histone deacetylases are important for gene regulation, metabolism, and longevity. A unique feature of these enzymes is their utilization of NAD + as a cosubstrate, which has led to the suggestion that Sir2 activity reflects the cellular energy state. We show that SIRT1, a mammalian Sir2 homologue, is also controlled at the transcriptional level through a mechanism that is specific for this isoform. Treatment with the glycolytic blocker 2-deoxyglucose (2-DG) decreases associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
141
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(149 citation statements)
references
References 52 publications
6
141
1
1
Order By: Relevance
“…S5 and data not shown). The reason for this lack of regulation remains unclear, and could be because there is no close C. elegans homologues of HIC-1, which was shown to be required for the transcription regulation of SIRT1 by CtBP (28). Together with the epistatic analysis, our results suggest that CTBP-1 does not regulate life span through up-regulation of SIR-2.1.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…S5 and data not shown). The reason for this lack of regulation remains unclear, and could be because there is no close C. elegans homologues of HIC-1, which was shown to be required for the transcription regulation of SIRT1 by CtBP (28). Together with the epistatic analysis, our results suggest that CTBP-1 does not regulate life span through up-regulation of SIR-2.1.…”
Section: Resultssupporting
confidence: 58%
“…Interestingly, previous studies show that a reduction in CtBP binding to the transcription repressor HIC-1 [hypermethylated in cancer (27)] results in an up-regulation of the human Sir2 homologue SIRT1 expression in primary fibroblasts (28), suggesting that SIRT1 may be a downstream target of CtBP. However, the expression of C. elegans sir-2.1 and other possible Sir2 homologues (sir-2.2, sir-2.3 and sir-2.4) was unaltered in the absence of a functional CTBP-1 in our study (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2B), recent reports revealed the existence of a nucleocytoplasmic shuttling mechanism for SIRT1 (24,50). Thus, our data strongly suggest that SIRT1 abundance and its localization, being sensitively influenced by ambient glucose levels, are also directly involved in the regulation of myogenesis as a prerequisite for regulating its enzymatic activity at suitable (55). These changes in SIRT1 abundance in skeletal muscle cells may contribute not only to myogenesis but also to metabolic adaptations during glucose deprivation, such as regulation of mitochondrial gene expression and fatty acid utilization (17,29).…”
Section: Discussionsupporting
confidence: 48%
“…Intriguingly, the repression of SIRT1 gene expression does not appear to be affected on the basis by functional HIC1 solely, but also by the availability of the redoxsensitive HIC1-corepressor CtBP and the concentration of NADH in the nucleus. The reduction of NADH results in impaired formation of HIC1-CtBP complexes, therefore leading to decreased HIC1-mediated repression, which is associated with increased SIRT1 gene expression independent of HIC1-status (Zhang et al, 2007). Moreover, previous studies reported an increase in SIRT1 protein in the liver of fasted mice while mRNA levels remained constant, suggesting that SIRT1 is regulated post-transcriptionally (Rodgers et al, 2005).…”
Section: Discussionmentioning
confidence: 94%